Localized surface plasmon resonance inflection points for improved detection of chemisorption of 1-alkanethiols under total internal reflection scattering microscopy - Kyeong Rim Ryu; Geun Wan Kim; Ji Won Ha (Scientific Reports, 2021)
Abstract Plasmonic gold nanoparticles are widely used in localized surface plasmon resonance (LSPR) sensing. When target molecules adsorb to the nanoparticles, they induce a shift in the LSPR scattering spectrum. In conventional LSPR sensing, this shift is monitored at the maximum of the LSPR scattering peak. Herein, we describe the sensitivity of detecting chemisorption of 1-alkanethiols with different chain lengths (1-butanethiol and 1-haxanethiol) on single gold nanorods (AuNRs) of fixed diameter (25 nm) and three different aspect ratios under a total internal reflection scattering microscope. For single AuNRs of all sizes, the inflection point (IF) at the long-wavelength side (or low-energy side) of the LSPR scattering peak showed higher detection sensitivity than the traditionally used peak maximum. The improved sensitivity can be ascribed to the shape change of the LSPR peak when the local refractive index is increased by chemisorption. Our results demonstrate the usefulness of tracking the curvature shapes by monitoring the homogeneous LSPR IF at the red side of the scattering spectrum of single AuNRs.